Genetically predicted iron status was associated with the risk of prostate cancer - Ying, Jiacheng; Wang, Binyan; Han, Shuyang; Song, Jie; Liu, Ke; Chen, Weiwei; Sun, Xiaohui; Mao, Yingying; Ye, Ding (Frontiers in Oncology, 2022)
Observational studies have reported a relationship between iron status and the risk of prostate cancer. To further clarify the underlying causal relationship, we conducted a Mendelian randomization (MR) analysis. We selected three genetic variants (rs1800562, rs1799945 and rs855791) closely correlated with four iron status biomarkers (serum iron, log-transformed ferritin, transferrin saturation, and transferrin) as instrumental variables. Summary statistics for prostate cancer were obtained from the PRACTICAL consortia including 79,148 cases and 61,106 controls of European ancestry. Genetically predicted increased iron status were associated with the decreased risk of prostate cancer, with odds ratio of 0.91 (95% CI: 0.84, 0.99; P = 0.035) for serum iron, 0.81 (95% CI: 0.65, 1.00; P = 0.046) for log-transformed ferritin, 0.94 (95% CI: 0.88, 0.99; P = 0.029) for transferrin saturation, and 1.15 (95% CI: 0.98, 1.35; P = 0.084) for transferrin (with higher transferrin levels representing lower systemic iron status), using the inverse-variance weighted method. Sensitivity analyses produced consistent associations and MR-Egger regression indicated no potential pleiotropy. Our replication analysis based on FinnGen research project showed compatible results with our main analysis. We also conducted a meta-analysis which similarly showed that serum ferritin (SMD: -1.25; 95% CI: -2.34, -0.16; P = 0.024) and transferrin saturation (SMD: -1.19; 95% CI: -1.19, -0.05; P = 0.042) were lower in patients with prostate cancer compared to controls. In conclusion, our current study suggests a protective role of iron in the risk of prostate cancer.